(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper provides Reliability that has to be implemented in the Client –Server communication in a network .The most important thing in client server communication is the reliability of data. In an online transaction all the data is transferred over the network there are several factors like hardware crisis or unavailability of network which prevent the total reliability factor. For this purpose it is required that the data should have a backup. Not only the data but the webserver can have these problem.Inorder to overcome these problems we merge the concept of mirroring of data with the help of a primary and secondary webserver. Each webserver runs independently on a different machine. The machine will have two NIC(NETWORK INTERFACE CARD) cards. In the server1 the first NIC card will be configured to the static ip which will be accessed by the client. In a point of failure the second NICin the primary server will be in communication with the first NICin the server2. When the query from the First NIC in server2 fails it assigns the static ip to the second NICin the server2. By this mechanism the client will have uninterrupted usage of the server even when the server2 fails.Another key aspect of this project is that it will take regular backup of the data in the database server to the secondary database server in which RAID 10 concept is used. This process will occur for a small interval of time as decided by the user. This paper use the RSA Algorithm to provide the Security to the client data during backup